2022
DOI: 10.1038/s41598-022-18120-z
|View full text |Cite|
|
Sign up to set email alerts
|

Revisiting implementation of multiple natural enemies in pest management

Abstract: A major goal of biological control is the reduction and/or eradication of pests using various natural enemies, in particular, via deliberate infection of the target species by parasites. To enhance the biological control, a promising strategy seems to implement a multi-enemy assemblage rather than a single control agent. Although a large body of theoretical studies exists on co-infections in epidemiology and ecology, there is still a big gap in modelling outcomes of multi-enemy biological control. Here we theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…There are not many extant studies that have explored this concept in the past, possibly because they are difficult to conduct due to many influencing factors [10]. Some of the studies write about the use of mixed species cover crops [11], others about the use of two different biological control agents (BCAs) concurrently [12][13][14][15][16], or just one BCA concurrently with different inert dusts in storage facilities [17][18][19]. Most studies found that a combined approach improves the effectiveness of pest control, while some report otherwise, indicating that this area of research is complex and there are many environmental and other factors contributing to the effectiveness of these approaches.…”
Section: Introductionmentioning
confidence: 99%
“…There are not many extant studies that have explored this concept in the past, possibly because they are difficult to conduct due to many influencing factors [10]. Some of the studies write about the use of mixed species cover crops [11], others about the use of two different biological control agents (BCAs) concurrently [12][13][14][15][16], or just one BCA concurrently with different inert dusts in storage facilities [17][18][19]. Most studies found that a combined approach improves the effectiveness of pest control, while some report otherwise, indicating that this area of research is complex and there are many environmental and other factors contributing to the effectiveness of these approaches.…”
Section: Introductionmentioning
confidence: 99%
“…There are not many extant studies that have explored this concept in the past, possibly because they are difficult to conduct with many influencing factors [10]. Some of the studies write about the use of mixed species cover-crops [11], others about the use of two different biological control agents (BCAs) concurrently [12][13][14][15][16], or just one BCA concurrently with different inert dusts in storage facilities [17][18][19]. Most studies found that a combined approach improves the effectiveness of pest control, while some report otherwise, indicating that this area of research is complex and there are many environmental and other factors contributing to the effectiveness of these approaches.…”
Section: Introductionmentioning
confidence: 99%